(untitled) - Gerke, Solvay (Bonn, 2009)
This paper focuses on the social interaction of paddy farmers and landless people during the annual flood season from a local knowledge perspective. It will be argued that local knowledge turns into a strategic resource in the context of growing competition for decreasing natural water products
Keywords: Knowledge management,Quản lý tri thức; Vietnam,Việt Nam